2023
DOI: 10.1186/s12985-023-02092-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological change of influenza virus in hospitalized children with acute respiratory tract infection during 2014−2022 in Hubei Province, China

Abstract: Purpose Influenza virus (IFV) causes acute respiratory tract infection (ARTI) and leads to high morbidity and mortality annually. This study explored the epidemiological change of IFV after the implementation of the universal two-child policy and evaluated the impact of coronavirus disease 2019 (COVID-19) pandemic on the detection of IFV. Methods Hospitalized children under 18 years with ARTI were recruited from Hubei Maternal and Child Healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The dynamics of IBV activity observed in our study was consistent with other places in China 13,16,17 . Beijing upgraded the NPIs like school and workplace closing, cancel public events, as well as restrictions on gatherings during 2021/2022 winter season to prevent the outbreak and spread of Omicron.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The dynamics of IBV activity observed in our study was consistent with other places in China 13,16,17 . Beijing upgraded the NPIs like school and workplace closing, cancel public events, as well as restrictions on gatherings during 2021/2022 winter season to prevent the outbreak and spread of Omicron.…”
Section: Discussionsupporting
confidence: 87%
“…The dynamics of IBV activity observed in our study was consistent with other places in China. 13,16,17 Beijing upgraded the NPIs like school and workplace closing, cancel public events, as well as restrictions on gatherings during 2021/2022 winter season to prevent the outbreak and spread of Omicron. Based on NPIs data set and generalized additive models, Zhang et al 5 reported that "cancelling public events" and "restrictions on internal travel" measures played an important role in the reduction of influenzalike illness.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly people are more susceptible to influenza because of their weakened immune function and prevalence of chronic diseases (2) . Elderly influenza patients often suffer from severe pulmonary infection, which aggravates organ disease and is one of the main causes of death (3) Influenza is a highly contagious respiratory viral illness that occurs in certain seasons of the year. The 2 main types of human influenza viruses are influenza virus A and influenza virus B, both of which are easily spread between elderly patients, and are responsible for seasonal influenza epidemics each year, with a significant disease burden and significant morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%